2016
DOI: 10.1021/acs.jpcc.5b11371
|View full text |Cite
|
Sign up to set email alerts
|

Au–Cu Alloyed Plasmonic Layer on Nanostructured GaN for SERS Application

Abstract: The main aim of this work was developing a novel technology for producing platforms for surface enhanced Raman scattering (SERS) measurements on photoetched (nanostructured) GaN with Au−Cu thin film as surface plasmonic layer. Dealloying of deposited Au−Cu films gives very stable and SERS-active platforms. Influence of percentage of copper in the alloyed Au−Cu layer on the SERS enhancement factor (EF SERS ) was examined. SERS measurements were performed using pyridine and 4mercaptobenzoic acid. Corresponding G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 46 publications
0
14
1
Order By: Relevance
“…Many materials for SERS measurements based on nanostructured GaN substrates containing the surface nanopillars shaped-like conical sheaves have been produced by Weyher et al (example morphologies of studied materials are shown in Figure 4 ). On such surface-nanostructured GaN substrates, gold [ 30 , 31 , 32 , 33 ], gold and silver alloy [ 34 ] or gold and copper alloy [ 35 ] were deposited. In this case, the nanostructuring of GaN surface was realized by pre-etching in a 10% HF solution and subsequent photo-etching using a 300 W xenon UV lamp in a solution of 0.02 M KOH and 0.02 M K 2 S 2 O 8 .…”
Section: Non-metallic Nanostructured Thin Films Covered By Plasmonmentioning
confidence: 99%
See 3 more Smart Citations
“…Many materials for SERS measurements based on nanostructured GaN substrates containing the surface nanopillars shaped-like conical sheaves have been produced by Weyher et al (example morphologies of studied materials are shown in Figure 4 ). On such surface-nanostructured GaN substrates, gold [ 30 , 31 , 32 , 33 ], gold and silver alloy [ 34 ] or gold and copper alloy [ 35 ] were deposited. In this case, the nanostructuring of GaN surface was realized by pre-etching in a 10% HF solution and subsequent photo-etching using a 300 W xenon UV lamp in a solution of 0.02 M KOH and 0.02 M K 2 S 2 O 8 .…”
Section: Non-metallic Nanostructured Thin Films Covered By Plasmonmentioning
confidence: 99%
“…The surface of GaN can be also nanostructured in another manner. For example, Weyher et al at first etched the surface of GaN in a molten eutectic KOH—NaOH mixture, which led to the creation of inverted pyramids on the surface of the GaN substrate, and then the previously described process of the creation of nanopillars shaped-like conical sheaves was realized [ 35 , 37 ]. In the next steps, AuCu alloy (40/60 at%) [ 35 ] or AuAg alloy (70/30 at%) [ 37 ] were deposited and the obtained films were further etched in nitric acid.…”
Section: Non-metallic Nanostructured Thin Films Covered By Plasmonmentioning
confidence: 99%
See 2 more Smart Citations
“…By virtue of their unique material properties, nanostructures of III-nitride materials have been of considerable interest for various applications including piezotronic sensing, ambient energy harvesting, nanostructurebased lighting and computing devices, etc. [1][2][3][4][5][6][7][8][9][10][11][12][13] Numerous types of nitride nanostructures have been explored via either templateassisted or template-free fabrication methodologies. [14][15][16][17] In the template-assisted strategy, material growth is carried out on sacrificial nanostructured template materials such as carbon nanotubes, polymers, or anodic aluminum oxide (AAO).…”
Section: Introductionmentioning
confidence: 99%